Waddles - McPhail, David, 1940- (New York : Abrams Books for Young Readers, 2011)
Waddles, a very plump and furry raccoon, helps his best friend Emily, a duck, hatch and raise her ducklings, and discovers what makes him truly happy.
Keywords: Raccoon -- Fiction; Ducks -- Fiction; Best friends -- Fiction; Friendship -- Fiction